(untitled) (Eurasian Scientific Herald, 2022)
This Article Presents An Analysis Of The Role And Importance Of CreativeCommunicative Skills In The Formation Of Professionalism In Higher Education. In Addition, The Problems On The Development Of Creative And Communicative Abilities Of The Individual Are Highlighted